Immunotherapy in oral cancer: Review - Papaioannou Despoina; Petsali Spyridoula; Ndreou Alida; Akritidou Fani; Zisis Vasileios; Kavvadas Dimitrios; Poulopoulos Athanasios; Karachrysafi Sofia; Andreadis Dimitrios (Balkan Stomatological Society, 2023)
Squamous cell carcinoma of the head and neck (HNSCC) is the sixth most prevalent malignant entity with a significant fatality rate. The International Agency for Research on Cancer reported in 2018 that there are approximately 350,000 newly diagnosed instances of oral cancer per year, amounting to a cumulative incidence of 4.0 per 100,000 people. The aim of this review was to investigate the biomarkers associated with immunotherapy in head and neck cancer, and in particular oral cancer, as well as their respective immunotherapeutic agents. An extensive review of the literature was carried through. Relevant articles were searched in Medline Pubmed, Web of Science and Google scholar. The inclusion criterion was that the article should be written in English, whereas the exclusion criterion was the opposite. The current standard of care (SOC) for disease that recurs locally and/or metastatic disease was, until recently, platinum-based chemotherapy plus cetuximab. A potential treatment option is the monoclonal antibody cetuximab, which extends median progression-free survival (PFS) as it targets the epidermal growth factor (EGFR). Last decade, research has shown that there are two mechanisms of tumor's microenvironment (the immune escape and the T-cell exhaustion) which are related to total survival from cancer. Consequently, scientists focused on immunotherapy, a new therapeutic approach that activates a patient's immune system to fight tumor cells. Immune checkpoint inhibitors (ICIs) are a category of immunotherapies that are extremely effective at reactivating the immune system's defence against cancer. Oral cancer immunotherapy could target two significant immune checkpoints, cytotoxic T-lymphocyteassociated protein 4 (CTLA-4) and programmed death-1 (PD-1).